Assessment and Correlation of Knee Ligament Injuries on MRI with Outerbridge Classification System - Fatima, Urooj; Noman, Ali; Nadeem, Zahira; Iqbal, Laiba; Waheed, Kashif; Iqbal, Faisal; Jahanzaib, Muhammad (Indus Journal of Bioscience Research, 2025)
Background: Knee ligament injuries, particularly to the ACL, PCL, MCL, and LCL, are common causes of joint instability and long-term functional impairment. MRI serves as the preferred imaging modality for accurately evaluating both ligamentous damage and associated cartilage degeneration. The Outerbridge Classification System provides a standardized method for grading cartilage lesions, originally via arthroscopy and now increasingly applied through MRI. Understanding the correlation between ligament injuries and cartilage damage is essential for early diagnosis, effective treatment, and prevention of osteoarthritis. Objective: This study aims to assess ligament injuries on MRI and correlate them with Outerbridge grades to improve diagnostic accuracy and guide clinical management. Methodology: This descriptive cross-sectional study is conducted over four months from December, 2024 to March, 2025 with a sample size of 64 participants, selected through convenience sampling. It includes sports-injured patients and patients with confirmed ligament injury. Patients with previous knee surgery, concurrent lower limb injuries, and chronic knee conditions are excluded to avoid confounding imaging findings. Results: Out of 64 patients, the majority present with ligament injuries involving the MCL (98.4%) and LCL (96.9%), followed by the PCL (67.2%) and ACL (28.1%). A significant association is observed between ligament injuries and higher Outerbridge cartilage grades, particularly Grades 3 and 4. Synovitis and joint effusion are also frequently identified. Cartilage degeneration is more prevalent in older age groups, and MRI effectively demonstrates both ligament and cartilage pathology. These findings support a strong correlation between ligamentous injury and progressive chondral damage. Conclusions: Ligament injuries, particularly involving the ACL, PCL, MCL, and LCL, are frequently associated with advanced cartilage damage. MRI proves to be a valuable tool for comprehensive knee evaluation, enabling early detection of both soft tissue injuries and degenerative changes.